Complete state‐wide outcomes in elective colon cancer surgery. Issue 11 (15th October 2018) - Faragher, Ian G.; Hong, Michael K.‐Y.; Stupart, Douglas; Watters, David A.; Yeung, Justin
Abstract : Background: Maintaining high standards in colon cancer surgery requires the measurement of quality indicators and the re‐allocation of resources to address deficiencies. We used state‐wide administrative data to determine the inpatient mortality for patients undergoing elective colon cancer surgery and to compare individual hospital rates. Methods: The Dr Foster Quality Investigator Tool was used to explore the Victorian Admitted Episodes Dataset for elective admissions for colon cancer surgery between 2012 and 2016. The inpatient mortality rate, 30‐day readmission rate and the proportion of patients with increased length of stay were measured. Risk‐adjusted rates were used to compare public and private hospitals. A peer group of 14 hospitals were studied using funnel plots to determine inter‐hospital variation in mortality. Results: There were 6120 colectomies performed for colon cancer in Victoria over 3 years. The crude inpatient mortality rate was 1.3%. It was significantly higher in public than private hospitals, even after risk adjustment. Variation in crude mortality was demonstrated among 14 selected hospitals. The lowest volume hospitals had significantly higher inpatient mortality rates. Right hemicolectomy was the commonest procedure performed. Conclusion: Using an efficient method of complete state‐wide data capture, we have demonstrated that the inpatient mortality rate after elective colon cancer surgery in Victoria is low. However, complexity remains around the interpretation of inter‐hospital variation, defining outliers, and comparing outcomes between public and private hospitals. Resolving these complexities and defining additional quality indicators remain a priority in the use of administrative data to audit the quality of colon cancer care.